Surviving competition: Neighborhood shops vs. convenience chains - Miguel Ángel Talamas Marcos (Inter-American Development Bank (IDB), 2023)
Hundreds of millions of microenterprises in emerging economies face increased competition from the entry and expansion of large firms that offer similar products. This paper studies how one of the world's most prevalent microenterprises, neighborhood shops, confront competition from convenience chains (e.g., 7- Eleven) in Mexico. To address the endogeneity in time and location of chain store openings, I pair two-way fixed effects with a novel instrument that, at the neighborhood level, shifts the profitability of chains but not of shops. An expansion from zero to the average number of chain stores in a neighborhood reduces the number of shops by 15%. This reduction is not driven by increased shop exits but by decreased shop entries. Shops retain their sales of fresh products and 96% of their customers, but customers visit shops less often and spend less on non-fresh and packed goods. The evidence suggests that shops survive by exploiting comparative advantages stemming from being small and owner-operated, such as lower agency costs, relationships with the community, broader and tailored product mix, and informal credit. The welfare gains of convenience chains replacing shops are increasing in household income.
Keywords: O10; D22; D25; D40; 330; development; microenterprise dynamics; competition; entry